HUBUNGAN MOTIVASI KERJA DENGAN KINERJA TENAGA KEPENDIDIKAN - Dahma Bagus Widodo; Ali Imron; Imron Arifin (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2019)
Abstract: This research aims to, (1) determine the motivation level to work of educational staff in the environment of faculties in State University of Malang, (2) determine the performance level of educational staff in the environment of faculties in State University of Malang, (3) determine the relationship of work motivation and performance of educational staff in the environment of faculties in State University of Malang. This research uses a quantitative approach with descriptive correlational design. The instrument of this research using a questionnaire respondents of the State University Malang environment. The analysis technique used in this research is descriptive analysis correlation. The results of this study indicate, (1) the motivation level to work of academic staff  in the faculties of the State University Malang environment consisting of job satisfaction and job dissatisfaction hygienes motivators classified in the good category, (2) the performance level of educational staff in the faculties of the State University Malang environment consisting of quality, quantity, the necessary supervision, attendance, and conservation classified in the high category, (3) there is a significant positive relationship between work motivation and performance of educational staff in the environment of faculties in State University of Malang.        Keywors: work motivation, employee performance, educational staff, college       Abstrak: Penelitian ini bertujuan untuk, (1) mengetahui tingkat motivasi kerja tenaga kependidikan di fakultas-fakultas lingkungan UM, (2) mengetahui tingkat kinerja tenaga kependidikan di fakultas-fakultas lingkungan UM, (3) mengetahui  hubungan motivasi kerja dengan kinerja tenaga kependidikan di fakultas-fakultas lingkungan UM. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan penelitian deskriptif korelasional. Instrumen penelitian ini menggunakan angket dengan responden tenaga kependidikan di fakultas-fakultas lingkungan UM. Teknik analisis yang digunakan dalam penelitian ini yakni analisis deskriptif korelasi. Hasil penelitian ini menunjukkan, (1) tingkat motivasi kerja tenaga kependidikan di fakultas-fakultas lingkungan UM yang terdiri atas job satisfaction motivator dan job dissatisfaction hygienes tergolong dalam kategori baik, (2) tingkat kinerja tenaga kependidikan di fakultas-fakultas lingkungan UM yang terdiri atas kualitas, kuantitas, supervisi yang diperlukan,  kehadiran, dan konservasi tergolong dalam kategori tinggi, (3) ada hubungan positif yang signifikan antara motivasi kerja dengan kinerja tenaga kependidikan di fakultas-fakultas lingkungan UM. Kata kunci: Motivasi kerja, kinerja pegawai, tenaga kependidikan, perguruan tinggi